ISSUES OF EFFECTIVE ORGANIZATION OF PRACTICAL CLASSES AND CLUBS IN MATHEMATICS IN TECHNICAL UNIVERSITIES - Abdunazarov, Rabimkul (Журнал иностранных языков и лингвистики, 2023)
The article discusses the issues of enriching the assignments of practical classes and science clubs with educational materials in the field, depending on the direction of education. Building a mathematical model for undergraduate students to calculate the volume of liquid in a container with a complex appearance according to the given parameters, common in everyday life, based on this model, the problem of creating mobile applications, online calculators can be solved effectively using online websites for direct mathematical calculations. The use of complex variable functions during problem solving increases students’ ability to work with complex numbers.